Mature Cystic Teratoma of the Fallopian Tube in a Postmenopausal Woman: A Case Report and Review of the Literature - Mustafa Erkan Sari; Ozhan Ozdemir; Pinar Kadirogullari; Funda Arpaci Ertugrul; Cemal Resat Atalay (Case Reports in Obstetrics and Gynecology)
Background. Mature cystic teratomas of the fallopian tube are extremely rare and only 54 cases have been reported in the literature. In this paper, we report a mature cystic teratoma of the fallopian tube in a postmenopausal woman and we report the review of literature of tubal cystic teratomas. Case. A 62-year-old, gravida 4 postmenopausal woman presented with pain in the right lower abdominal region for a long time. An 88 × 72 × 95 mm heterogeneous mass which contained calcifications and lipoid components was detected in the right adnexal region by transvaginal ultrasonogram (TV-USG). Serum tumour markers, namely, CA125, CA15-3, and CA19-9, were within normal range. A laparotomy revealed a 9 × 10 cm cystic mass within the fimbrial region in the right fallopian tube, and right salpingoopherectomy was performed consequently. Microscopic examination revealed squamous epithelium with sebaceous glands and hair follicles, and pseudostratified ciliated respiratory epithelium with cartilage and mucous glands. Because the frozen section resulted in a benign dermoid cyst, no further operative procedure was performed. The postoperative follow-up was uneventful and the patient was discharged on the second postoperative day. Conclusion. In cases of undetermined pelvic or abdominal masses, a teratoma of the fallopian tube should be considered.